Urinary paranitrophenol, a metabolite of methyl parathion, in thai farmer and child populations - Parinya Panuwet (2018)
Human exposure to methyl parathion can be assessed by measuring the concentration of its metabolite paranitrophenol (PNP) in urine. Our biologic monitoring study in Chiang Mai, Thailand, measured PNP and dialkylphosphate metabolites (i.e., dimethylphosphate [DMP] and dimethylthiophosphate [DMTP]) of methyl parathion in urine samples collected from 136 farmers (age 20 to 65 years) and 306 school children (age 10 to 15 years) in 2006. Participants came from two topographically different areas: one was colder and mountainous, whereas the other was alluvial with climate fluctuations depending on the monsoon season. Both children and farmers were recruited from each area. Despite methyl parathion's prohibited use in agriculture in 2004, we detected PNP in >90% of all samples analyzed. We applied a nonparametric correlation test (PNP vs. DMP and DMTP) to determine whether the PNP found in most of the samples tested resulted from exposures to methyl parathion. DMP (Spearman's rho = 0.601 [p = 0.001] for farmers and Spearman's rho = 0.263 [p <0.001] for children) and DMTP (Spearman's rho = 0.296 [p = 0.003] for farmers and Spearman's rho = 0.304 [p<0.001] for children) were positively correlated with PNP, suggesting a common source for the three analytes, presumably methyl parathion or related environmental degradates. Although we found a modest correlation between the metabolites, our findings suggest that despite the prohibition, at least a portion (approximately 25% to 60%) of the PNP detected among farmers and children in Thailand may be attributed to exposure from continued methyl parathion use. © 2009 Springer Science+Business Media, LLC.